Taurine reverses sodium fluoride-mediated increase in inflammation, caspase-3 activity, and oxidative damage along the brain-pituitary-gonadal axis in male rats (2017)
Excessive exposure to fluoride is associated with male reproductive dysfunction in humans and animals. Taurine (2-aminoethane sulfonic acid) is a free intracellular β-amino acid with antioxidant, anti-inflammatory, and neuroprotective properties. However, the effect of taurine on fluoride-induced reproductive toxicity has not been reported. The present study investigated the influence of taurine on sodium fluoride (NaF)-induced functional changes along the brain–pituitary–gonadal axis in male rats. NaF was administered singly in drinking water at 15 mg•L⁻¹ alone or orally co-administered by gavage with taurine at 100 and 200 mg•kg⁻¹ body mass•day⁻¹ for 45 consecutive days. Results showed that taurine significantly prevented NaF-induced increases in oxidative stress and inflammation levels in the brain, testes, and epididymis of the treated rats. Moreover, taurine reversed NaF-induced elevation in inflammatory biomarkers and caspase-3 activity as well as histological damage in the brain, testes, and epididymis of the treated rats. The significant reversal of NaF-induced decreases in testosterone level and testicular activities of acid phosphatase, alkaline phosphatase, and lactate dehydrogenase by taurine was accompanied by enhancement of sperm functional characteristics in the treated rats. Taurine may be a possible chemopreventive candidate against reproductive dysfunction resulting from fluoride exposure.